A Multifaceted Nursing Practice Bundle for the Management of Changed Behaviour in Hospitalised Adults With Cognitive Impairment: A Pre‐/Poststudy - Erin Rachel Davis; Christina Aggar; Michelle Bissett (Australasian Journal on Ageing, 2026)
ABSTRACT Objective The aim of this study was to evaluate changes in nursing practices following implementation of a multifaceted nursing practice bundle for the management of changed behaviour in hospitalised adults with cognitive impairment. Methods A single‐group pre–post interventional study evaluated changes in nurses' reactions to changed behaviour and the use of alternatives to physical restraint following implementation of a multifaceted nursing practice bundle (implementation framework, nurse education and nonpharmacological resources). Results Management of changed behaviour improved, with nurses more commonly reacting with care and less likely to react by ignoring when changed behaviour occurred. Nurses were also more likely to utilise professional knowledge and problem‐solving abilities, and less likely to use medications as alternatives to physical restraints. Conclusions The implementation of a nursing practice bundle was associated with improved management of changed behaviour in hospitalised adults with cognitive impairment, likely due to its multifaceted approach. Improvements in nursing practice indicate enhanced attitudes towards adults with cognitive impairment and increased confidence in implementing nonpharmacological interventions.